Impact of Covid-19 on Emergency Airway Management - Faris Suleiman Saleh Aldobekhi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The main and serious problem associated with COVID19 is pneumonia and the sequelae acute respiratory distress syndrome. For this, airway management and respiratory care is of prime importance especially as an emergency COVID-19 disease care protocol. There are various emergency airway modalities that are available for such patients. Objectives : The aim of this review was to determine the benefits and drawbacks of the various airway management methods that have surfaced as game changers in COVID19 respiratory distress. Methodology: A thorough search was conducted across several databases, using mesh keywords and the boolean algorithm,. After removing duplicates, relevant literature was chosen, and studies were chosen for a qualitative review based on the available research on the issue. Results : It was observed that in mild to severe situations, HFNC improves oxygen saturation, but it cannot be used as the primary dependent modality. If fully achieved, awake proning is linked to better oxygenation and lower mortality. Although invasive ventilation saves lives, weaning is difficult, and significant mortality is seen in the elderly and those with comorbidities. Conclusion: It is concluded that the type of respiratory distress, age, resources available in the setting, ability of the person in charge, and comorbidities be considered when choosing an emergency airway management therapy/modality. The efficacy of the modalities utilised in emergency airway care and acute respiratory distress due to COVID19 Pneumonia can be better explained by a complete and exclusive systematic review and meta-analysis.